Kajian Yuridis Kejahatan Cyber Bullying Di Media Sosial - Lasamahu, Julio; Sopacua, Margie Gladies; Fadillah, Astuti Nur (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Cyber bullying or bullying in cyberspace is an intentional act of intimidation, humiliation, humiliation or harassment via the internet. One typical example was experienced by FS, where the victim received deliberate insults from the perpetrato, through posts on the perpetrator's social account (FB). Purposes of the Research: this research aims to examine and discuss the elements of the criminal act of cyber bullying and the application of criminal sanctions against performers of cyber bullying.Methods of the Research: This research uses a normative juridical research method with the legal materials used, namely primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques were carried out through literature study and analyzed using qualitative methods to answer the problems in this researchResults / Findings / Novelty of the Research: The results of this research explain that Cyber bullying is a bullying behavior or annoying behavior, continuously harassing or causing trouble to someone through the internet or cyberspace, such as spreading disputes, harassment, defamation, these actions comply with the formulation of article 27 paragraph (3 ) ITE Law. One of them is insulting or defaming which can make the perpetrator threatened with article 27 paragraph (3) and threatened with imprisonment for a maximum of 4 (four) years and/or a fine of a maximum of IDR 750,000,000.00 (seven hundred and fifty million rupiah). The crime of cyber bullying cannot be completely eradicated, but it can be prevented by starting from oneself, and this crime should not be ignored and considered a joke, but we must better understand the impact of the crime of cyber bullying itself